Infective endocarditis due to Achromobacter xylosoxidans: A case report and a literature review - Oktania Candrawati; Indah Kartika Murni; Osman Sianipar (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Congenital heart disease (CHD) and invasive cardiac procedures are risk factors for infective endocarditis (IE) in children. IE with Achromobacter xylosoxidans is a rare case and has a high mortality rate. This case report and literature review aim to understand the risk factors, diagnosis, therapy, and outcome of IE wirh Achromobacter xylosoxidans. We observed a 14-months-old boy with ventricular septal defect (VSD), a history of cardiac catheterization, 9 days fever and febrile convulsion; and tachycardia and pansystolic murmur on the tricuspid valve were found. Transthoracic echocardiography revealed vegetation on the tricuspid valve. Monomicrobial clinical isolates of Achromobacter xylosoxidans were consistently found in three samples of aerobic blood culture bottles. The patient was treated with definitive antibiotic therapy with 200 mg/8 hours of ceftazidime for 21 days. Bacterial growth was not found in the blood culture evaluation which was performed after 48 hours of the therapy. Also, it was found that in the follow up period the patient had no fever on the sixth day, and the vegetation size was reduced. A patient with CHD, especially with VSD as an underlying condition who had a history of cardiac catheterization and accompanied by fever and heart murmur, should be suspected of having IE. Then the definitive antibiotic therapy with ceftazidime contributed to a better clinical outcome.